Pengembangan Modul IPA Berbasis Kontekstual Berbantuan Aplikasi Adobe Flash pada Siswa Kelas V SD - Wahyu Sholeh Munandar; Aren Frima; R. Angga Bagus Kusnanto (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to develop a product in the form of Development of Contextual-Based Science Modules Assisted by Adobe Flash Applications for Fifth Grade Students of SD Negeri Rejosari in accordance with the 2013 curriculum and to produce Contextual-Based Science Modules Assisted by Adobe Flash Applications that are valid, practical and effective for use in learning. This research is a development research with four-D development model. Based on the results of the assessment analysis by the three experts, namely: linguist, 0.75 media expert 0.87 and 0.89 material expert, it shows that the Contextual-Based Science Module Assisted by Adobe Flash Application on animal and human movement organs fulfills the very valid criteria. While the results of the research on teacher practicality sheets obtained an average of 68,57% and students consisting of 6 people obtained an average of 68,09% that the Contextual-Based Science Module Assisted by Adobe Flash Applications met the practical criteria. And the results of the study on the effectiveness of all fifth grade students showed that the Contextual-Based Science Module Assisted by Adobe Flash Applications met the Medium criteria with a final score of 0.6, so it can be concluded that the Contextual-Based Science Module Assisted by Adobe Flash Applications met the criteria of being valid, practical and effective and could be used in learning. Keywords: Adobe Flash, Science Module, Development, Elementary School.